Extending the Stieltjes Transform - Nemzer, Dennis (Sarajevo Journal of Mathematics, 2024)
The classical Stieltjes transform is extended to a subspace of Boehmians. The transform is shown to be an analytic function in the half-plane $Re$ $z > 0$. Some Abelian type theorems are established. 2010 Mathematics Subject Classification. 44A15, 46F12, 44A10.